Effect of furosemide on muscle cramps in patients with liver cirrhosis. Issue 1 (16th August 2019) - Sawada, Yasuhiko; Kawaratani, Hideto; Kubo, Takuya; Fujinaga, Yukihisa; Furukawa, Masanori; Saikawa, Soichiro; Sato, Shinya; Takaya, Hiroaki; Kaji, Kosuke; Shimozato, Naotaka; Moriya, Kei; Namisaki, Tadashi; et al.
Abstract: Background and Aim: Patients with cirrhosis usually experience muscle cramps of varying severity. Although diuretics have been reported to cause muscle cramps, clinical evidence is limited. Also, it has been pointed out that the use of diuretics is associated with the progression of sarcopenia in patients with cirrhosis. We conducted a questionnaire survey to clarify the effects of diuretics and skeletal muscle loss on muscle cramps. Methods: Overall, we enrolled 152 adults with cirrhosis in this study. Cramp questionnaires were obtained after informed consent. Study variables (demographics, physical findings, serum metabolic panel, and drugs taken that affect muscle cramps) were extracted from medical records. Body composition, including muscle volume, was analyzed using a bioelectrical impedance analysis method, and muscle strength (handgrip) was evaluated at enrollment. Cross‐sectional skeletal muscle area was evaluated on computed tomography imaging at the L3 vertebral level to investigate the relationship between muscle cramps and sarcopenia. Results: The proportion of furosemide administration was higher in patients with cramping compared with those without. On a multivariate logistic regression analysis, furosemide use was a significant factor in the presence of muscle cramps. Furthermore, regarding factors contributing to muscle cramp severity, furosemide use was extracted by multivariate logistic regression analysis. In the presence or severity of muscle cramps, skeletal muscles did not show any significant difference. Conclusions: Furosemide use for patients with cirrhosis was considered a risk factor for occurrence and severity of muscle cramps. On the other hand, skeletal muscle mass loss was not associated with muscle cramps.